Confidence game : how a hedge fund manager called Wall Street's bluff - Richard, Christine S. (Wiley/John Wiley & Sons, Inc., 2010)
"Confidence Game tells the story how hedge fund manager Bill Ackman's warnings regarding bond insurer MBIA's credit rating went unheeded as Wall Street careened toward disaster"--Provided by publisher.